2007
DOI: 10.1371/journal.pbio.0050047
|View full text |Cite
|
Sign up to set email alerts
|

LACHESIS Restricts Gametic Cell Fate in the Female Gametophyte of Arabidopsis

Abstract: In flowering plants, the egg and sperm cells form within haploid gametophytes. The female gametophyte of Arabidopsis consists of two gametic cells, the egg cell and the central cell, which are flanked by five accessory cells. Both gametic and accessory cells are vital for fertilization; however, the mechanisms that underlie the formation of accessory versus gametic cell fate are unknown. In a screen for regulators of egg cell fate, we isolated the lachesis (lis) mutant which forms supernumerary egg cells. In l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
212
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 155 publications
(225 citation statements)
references
References 26 publications
6
212
1
Order By: Relevance
“…Mutation in LIS that shows homology to the S. cerevisiae SF PRP4, an integral part of the U4/U6 complex, resulted in supernumerary egg cells implicating splicing in cell fate decisions (Gross-Hardt et al, 2007). CLO/GAMETOPHYTIC FACTOR1 (GFA1) encodes a homolog of Snu114p/U5-116kDa protein and physically interacts with At-Brr2 and At-Prp8, the putative U5 snRNP components of Arabidopsis (Moll et al, 2008;Liu et al, 2009).…”
Section: Function Of Sfs In Developmentmentioning
confidence: 99%
“…Mutation in LIS that shows homology to the S. cerevisiae SF PRP4, an integral part of the U4/U6 complex, resulted in supernumerary egg cells implicating splicing in cell fate decisions (Gross-Hardt et al, 2007). CLO/GAMETOPHYTIC FACTOR1 (GFA1) encodes a homolog of Snu114p/U5-116kDa protein and physically interacts with At-Brr2 and At-Prp8, the putative U5 snRNP components of Arabidopsis (Moll et al, 2008;Liu et al, 2009).…”
Section: Function Of Sfs In Developmentmentioning
confidence: 99%
“…The cellularization and differentiation of cells in the embryo sac appear to be transcriptionally regulated (Rabiger and Drews, 2013), and mechanisms involving RNA splicing and auxin and peptide signaling specify female gametic cells (Gross-Hardt et al, 2007;Pagnussat et al, 2009;Lieber et al, 2011;Lituiev et al, 2013). For male germline development, a regulatory framework for cell cycle progression and gamete specification has been established Borg and Twell, 2010;Twell, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In maize, small peptides have been identified that, owing to their size, have the potential to move between cells (Dresselhaus, 2006). A further hint for communication between single female gametophytic cells comes from the analysis of the lachesis (lis) mutant (Groß-Hardt et al, 2007). lis mutants form supernumerary egg cells, resulting from misspecification of the synergids and central cell, which express morphological and molecular attributes of the egg cell.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, antipodal cells adopt a central cell fate in lis mutants, demonstrating that all cells in the female gametophyte can differentiate into gametic cells. lis is defective in the Arabidopsis homologue of the yeast pre-mRNA splicing factor PRP4 (Groß-Hardt et al, 2007), and promoterreporter analysis has suggested that cell specification in wild-type female gametophytes correlates with a strong upregulation of LIS expression in gametic cells. By contrast, LIS expression appears to be downregulated in accessory cells of mature female gametophytes, which has led to the hypothesis that the gametic potential of accessory cells is repressed by lateral inhibition from the gametic cells (Groß-Hardt et al, 2007).…”
Section: Introductionmentioning
confidence: 99%